Pengaruh Pemberian Ekstrak Sargassum sp. dengan Pelarut Metanol pada Pakan terhadap Jumlah Eritrosit dan Differensial Leukosit Ikan Lele Dumbo (Clarias gariepinus) [Effect Of Extract Sargassum sp. with Methanol Solvent in Feed on Erythrocythes and Differential Leucocythes of African Catfish (Clarias gariepinus) ] - Firly Waliani Rahma; Gunanti Mahasri; Laksmi Surmartiwi (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract The main obstacles in successful production is the attack of a disease. Preventive measures in reducing disease one of them is by means an increase in immunity the body of fish use natural compound (Parelberg et al., 2005). One of the natural compound that can be used as obtaining the immune system fish are the vitamin C, iodine, tannin (Bachtiar, dkk., 2012) and polysaccharides and derivatives as fucoidan. (Castro et. al., 2006) which is in Sargassum sp. With the provision of extract Sargassum sp. in feed is expected to optimize the number of erythrocytes and differensial leukocytes (number of neutrophils , monocytes and lymphocytes) at african catfish (Clarias gariepinus) so that it may optimize immunity the body of fish (Brown, 2000). The result of the observation of the blood of fish test is the use of extract Sargassum sp. wich get mixed in feed with doses 5, 10 and 15 g/kilogram feed during 21 days impact on the number of erythrocytes and prosentase lymphocytes blood catfishes. In doses C (15 g extract/ kilogram feed) put a value erythrocytes highest in day 21 namely 16.84 ± 1.56 x 105 cells/mm3, and give prosentase lymphocytes highest in day 21 than those wich others are 86.00 ± 3.81 %. But in a post test, B and C not seen the real difference between treatment. While for statistics the addition of extract not indicates the influence of real to the percentage neutrophils and monocytes of the blood fish. So that it can be said that addition extract Sargassum sp. with doses 15 g extract/kilogram feed give the effectiveness of the optimal response immune system than second doses other.